OVERVIEW OF INCOME TAX ON MORE VAT DIFFERENCES IN RETAIL USED MOTORCYCLE RETAIL - Nur Azizah, Waidatin; Suparna Wijaya (Dinasti Publisher, 2020)
The delivery of sale secondhand motorized retail of which is subject to a value-added tax of the output of 10% of the business circulation. According to regulations, Taxable Entrepreneurs may only credit input taxes of 90% of the output VAT. Therefore, VAT paid to the state is only 1% of business circulation, so there is a difference of more than 9% of business circulation. According Law Number 36 the Year 2008, this excess is income so that it can be subject to income tax. However, no regulation confirms this. So this research was conducted. The purpose of this study was to determine aspects of income tax on the excess of value-added tax on the sale or delivery of used motor vehicles in retail. The method used in this research is descriptive qualitative. The results of this study are the difference in value-added tax on the delivery of used motor vehicles is income.